HUBUNGAN EDUKASI E-LEAFLET TERHADAP PENGETAHUAN SISWA TENTANG ANEMIA REMAJA DI SMK SEHATI TAHUN 2023 - Euis Atikah,; Rina Dwi Anggraeni,; Dewi Rubi Fitriani, (Journal of Innovation Research and Knowledge, 2023)
Until now, the prevalence of anemia in adolescents is still high. Based on Riskesdas data in 2018 obtained the proportion of anemia in the age group of 15-24 years is 32% while the proportion of anemia in pregnant women aged 15-24 years is 84.6%. This community service activity aims to improve female students' knowledge about anemia and its prevention efforts. This activity is carried out by the method of Quasy Experimental with the provision of pre-test and post-test. Educational activities are carried out with two events providing material through e-leaflets and using leaflets. The number of participants in this activity is 50 people who are divided into 25 people for each group. The results showed that the provision of education through e-leaflet was more effective in increasing students' knowledge related to anemia compared to leaflet media. The results of the statistical test showed that there was a difference in knowledge about anemia in female students after being given education on e-leaflet and leafleting media with a p value of 0.015. The most influential media effectiveness in increasing female students' knowledge about anemia is by using e-leaflet media